ARABIC THEATER IN EARLY KHEDIVIAL CULTURE, 1868–72: JAMES SANUA REVISITED. (14th February 2014) - Mestyan, Adam
Abstract: This article revisits the official culture of the early khedivate through a microhistory of the first modern Egyptian theater in Arabic. Based on archival research, it aims at a recalibration of recent scholarship by showing khedivial culture as a complex framework of competing patriotisms. It analyzes the discourse about theater in the Arabic press, including the journalist Muhammad Unsi's call for performances in Arabic in 1870. It shows that the realization of this idea was the theater group led by James Sanua between 1871 and 1872, which also performed ʿAbd al-Fattah al-Misri's tragedy. But the troupe was not an expression of subversive nationalism, as has been claimed by scholars. My historical reconstruction and my analysis of the content of Sanua's comedies show loyalism toward the Khedive Ismail. Yet his form of contemporary satire was incompatible with elite cultural patriotism, which employed historicization as its dominant technique. This revision throws new light on a crucial moment of social change in the history of modern Egypt, when the ruler was expected to preside over the plural cultural bodies of the nation.